Pengembangan Sistem Pakar Diagnosa Penyakit Asma Dengan Metode Forward Chaining Berbasis Android - Suherman Suherman (Jurnal SIGMA, 2020)
Expert system is a branch of artificial intelligence that learns how to adopt the way an expert thinks and reason in solving a problem, and makes a decision or draws conclusions from a number of facts. Until now there have been several results of the development of expert systems in various fields according to one's expertise. In this study a system application will be designed experts to diagnose asthma. The development of an expert application system for asthma diagnosis is one of the applications of a computerized system in the field of medicine. The aim of this research is to develop a medical knowledge-based system in diagnosing asthma that can be displayed in expert system-based application software. So that it can simplify the counseling process for ordinary people to know the early detection of symptoms of asthma and solutions or treatments that can be done independently. The reasoning of this expert system application uses forward chaining inference techniques. Where in this forward chaining begins with the initial information (initial symptoms) and moves forward to match further information until finding information in accordance with the rules, then will conclude in the form of a description of the type of disease and solution. In developing expert systems, conventional approaches to methodology will be used Expert System Development Life Cycle (ESDLC) from Durkin (1994). The results of this research are the application of an expert system for diagnosing asthma has facilities that can help extension workers in providing counseling to the public to find out early detection of symptoms of asthma, based on the type of asthma that attacks and solutions or ways of treatment that can be done independently. Keywords : ESDLC, forward chaining, asthma, expert system.